Critical Communication Pedagogy in/about/through the Communication Classroom - Kathryn B. Golsan; C. Kyle Rudick (Central States Communication Association, 2018)
Critical Communication Pedagogy (CCP) signals a critical approach to Communication and Instruction scholarship. Critical signals a recognition that social reality is inherently political and encourages individuals to work with/in communities to identify, intervene into, and change oppressive systems. Communication and Instruction scholarship refers to (a) research concerning how to teach communication principles, theories, or knowledge (i.e., Communication Pedagogy or Communication Education) and (b) research about communication as it manifests in or about all types of educational spaces (i.e., Instructional Communication). CCP is not guided by a single methodology; rather, it signifies both an intellectual tradition and an umbrella term for critical approaches to Communication Pedagogy and Instructional Communication.